Granulation and Convectional Driving on Stellar Surfaces - Johannes Tschernitz; Philippe-A. Bourdin (The Astrophysical Journal Letters)
Surface convection is important for the presence of magnetic activity at stars. So far, this convection is thought to be a result of heating from below, where convection cells rise and break up. New models reveal that surface convection is instead strongly driven by cooling from above. We compare two simulations of surface convection, one with a significant heating from below and one without. We obtain surface convection in both cases, and they show similar granulation patterns. The deep convection driven by heating from below is still evolving and asymptotically approaches a steady-state solution. We find that convection from below is not needed at all to form typical photospheric granulation. This indicates the possibility of a surface dynamo acting on stars without a convecting envelope. Even stars without a convecting envelope could therefore exhibit stronger magnetic and coronal activity than expected so far.